2013
DOI: 10.1007/s12975-013-0270-5
|View full text |Cite
|
Sign up to set email alerts
|

Deferoxamine Reduces Neuronal Death and Hematoma Lysis After Intracerebral Hemorrhage in Aged Rats

Abstract: Intracerebral hemorrhage (ICH) is primarily a disease of the elderly. Deferoxamine (DFX), an iron chelator, reduces long-term neurological deficits and brain atrophy after ICH in aged rats. In the present study, we investigated whether DFX can reduce acute ICH-induced neuronal death and whether it affects the endogenous response to ICH (ferritin upregulation and hematoma resolution) in aged rats. Male Fischer 344 rats (18 months old) had an intracaudate injection of 100 μL autologous whole blood into the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 41 publications
(46 reference statements)
4
59
0
Order By: Relevance
“…Iron overload caused by ICH is an important contributor to neurobiological deficits, brain edema, inflammation, neuron apoptosis and brain atrophy. These effects can be reduced with deferoxamine, an iron chelator [38][39][40][41][42][43][44][45] . However, two studies [46,47] have reported that deferoxamine reduces the level of iron, but does not improve outcomes, in a collagenase-induced ICH model.…”
Section: Discussionmentioning
confidence: 99%
“…Iron overload caused by ICH is an important contributor to neurobiological deficits, brain edema, inflammation, neuron apoptosis and brain atrophy. These effects can be reduced with deferoxamine, an iron chelator [38][39][40][41][42][43][44][45] . However, two studies [46,47] have reported that deferoxamine reduces the level of iron, but does not improve outcomes, in a collagenase-induced ICH model.…”
Section: Discussionmentioning
confidence: 99%
“…DFX can reduce free iron in cerebrospinal fluid as well as ICH-induced neurological deficits and acute neuronal death in rat experiment. It can also inhibit the endogenous response to ICH and the upregulation of ferritin and AQP4, which are related to a poor outcome of ICH [46,89,90] . Pro-oxidant heme, which is released from Hb catabolism of heme, plays an important role in the resolution of hematoma.…”
Section: Inhibition Of Rbcs Lysis and Hb Toxicitymentioning
confidence: 99%
“…Blood lysis starts at 24 h and continues for the next several days, leading to the release of cytotoxic hemoglobin (Hb) with further deterioration of the pathological status quo [2]. Iron, a major hemoglobin degradation product which accumulates in the brain parenchyma for months, has a detrimental effect in secondary injury [3][4][5][6][7]. Iron plays a key role in edema formation and cell death after ICH [5,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exogenous iron chelation therapy seems to be a logical approach to remove toxic levels of iron. Deferoxamine, a ferric iron chelator, which is the most popular treatment in experimental intervention strategy in ICH, has been shown to mitigate iron-mediated damage [3,4]. Unfortunately, recent data showed that deferoxamine can reduce the iron contents in the brain, but could not attenuate injury and improve neurological outcome [10,11].…”
Section: Introductionmentioning
confidence: 99%